USM COMMITTED TOWARDS PRODUCING MORE GRADUATES IN TRANSLATION AND INTERPRETATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 16 October 2016 – Universiti Sains Malaysia (USM) through the Translation and Interpretation Studies offered by USM School of Humanities (PPIK) would remain committed in producing more translators and interpreters to fill the demands of the market requiring a professional workforce in the field of translation and interpretation and having global potential.